Strategi Pengembangan Sektor Pertanian Dan Pertambangan Di Provinsi Jambi - bahri, zainul; Roihan, Muhammad; Rosyid, Garry Yuesa; Muhammad Ridwan; Indriyani Setyawati; Vinni Aprilianti (Brida Provinsi Jambi, 2026)
This study aims to identify economic sectors with comparative and competitive advantages and to analyze structural economic shifts supporting economic growth in Jambi. In addition, the study formulates development strategies for the agricultural and mining sectors as the region’s leading sectors. The research employs a mixed-methods approach, combining quantitative and qualitative analyses using SLQ, DLQ, Esteban-Marquillas Shift-Share, and SWOT analysis. The data used consist of (GRDP) at constant prices for the period 2011–2024. The findings indicate that the agriculture, forestry, and fisheries sector, along with the mining and quarrying sector, constitute base sectors with strong competitive advantages. The economic structure of Jambi Province remains dominated by primary sectors and has not yet undergone a significant transformation toward industrial and service sectors. The SWOT analysis places the leading sectors in Quadrant I (aggressive strategy), indicating substantial development opportunities through downstream industrialization policies, technological modernization, and strengthened environmental governance. These findings provide a strategic foundation for formulating sustainable and competitive regional economic development policies.